Efforts Towards a More Anticipatory Design for Disasters in Housing and Landscape Planning - Deva Fosterharoldas Swasto; Cantya Paramita Marhendra (The Indonesian Journal of Planning and Development, 2025)
Indonesia has a high risk of natural disasters, especially earthquakes and tsunamis along the coast. Since the 2004 tsunami in Aceh, there has been an increasing awareness of the need for housing and landscape planning that anticipates these disasters. Poor design and quality of housing and landscape environments often lead to fatal impacts when disasters occur, especially in areas where the environment is not responsive to surrounding conditions. This paper analyzes several planning aspects related to these conditions through theoretical and empirical approaches, particularly in residential environmental design and landscape. These conditions are derived from technological rules or principles. It is also expected that examples or lessons from other countries can contribute additional discourse to the writing. From analysis, findings that can be found and proposed are responses to the technological-physical aspects of buildings (i.e. safety and responsiveness), micro-scale housing and landscape design (i.e. building units, clusters, and variety of vegetation), housing and landscape planning at the macro-scale (i.e. land zoning and green proportions), as well as environmental support (i.e. environmental utility, accessibility, and protective landscape).